Barvna osvetlitev - Potrč, Matjaž (Analiza: časopis za kritično misel, 2023)
Chromatic IlluminationSome cases of chromatic illumination are presented. The question about the importance of chromatic illumination for epistemology is then approached. There is a tension between the epistemic experiential evidence and the richness of morphological content, a tension dissolved through chromatic illumination. Understanding of chromatic illumination efficacy is facilitated through “iceberg epistemology.” Above the waterline there is occurrent conscious cognitive intentional content. Under the water surface, there is a plurality of nonconscious intentional contents, which are not represented in the overwater scene. They are rather appreciated there, through the mediation of their features, illuminating the mentioned scene and providing attitudinal direction of the overwater surface intentional content. The deepest area of iceberg epistemology is due to its unconscious part, providing causal efficacy to the overwater scene, being experienced in an outof-the-blue manner. We propose that the area of epistemic justification in belief formation follows normative diversity in the ethical appropriateness judgment: The difference between the good and the right may be compared to objective epistemic propositional justification and doxastic belief justification with the epistemic agent’s engagement.
Keywords: chromatic illumination; iceberg epistemology; non-conscious and unconscious; the structure of belief formation; agent and epistemic system; normative diversity in epistemology